Combining O-LCA and O-LCC to support circular economy strategies in organizations: Methodology and case study. (15th February 2022) - Alejandrino, Clarisa; Mercante, Irma T.; Bovea, María D.
Abstract: The pathway to sustainable development requires the transition from a linear economy to a circular economy (CE). For this transition to succeed, it is necessary for all kinds of organizations to participate actively by integrating CE into their daily activities. Today, the identification and selection of possible CE improvements for industrial organizations remains a challenge. The aim of this paper is to propose and apply a methodology capable of evaluating and prioritizing CE strategies at the organizational level based on their environmental and economic performance (eco-efficiency). The methodology was built on the integration of the existing environmental life cycle assessment of organizations (O-LCA) and the proposed life cycle costing of organizations (O-LCC). As a case study, an industrial organization dedicated to the manufacture of construction products was assessed using mainly primary data for the environmental and economic analysis. After an initial diagnosis, ten CE improvement options were selected and arranged into eight alternative scenarios. Their application to the case study showed that although all the alternative scenarios were beneficial from the CE perspective, the environmental and economic effects presented different outcomes. The automation of the curing process was the most eco-efficient scenario, followed by internal material recirculation and energy efficiency. The conclusion was that it was possible to combine environmental and economic assessment with circular indicators to ensure the effective and efficient transition of the organization under study toward circularity. Graphical abstract: Image 1 Highlights: Circular Economy (CE) strategies at organizational level are selected. A methodology to prioritize CE strategies by means of their eco-efficiency is proposed. Existing organizational life cycle assessment (O-LCA) methodology is applied. Proposed organizational life cycle costing (O-LCC) methodology is applied. A case study of an Argentinian industrial organization is presented.